THE ROLE OF ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION LANGUAGE TEACHING - Suyarova Mavjuda Ergashevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Artificial Intelligence (AI) has become one of the most influential technological innovations in modern education. In higher education, especially in language teaching, AI is reshaping traditional pedagogical approaches by introducing personalized learning systems, intelligent tutoring, automated assessment, and interactive communication tools. This paper analyzes the role of AI in language education, its pedagogical benefits, challenges, and future development trends. The study shows that AI significantly improves learning efficiency, student motivation, and teacher productivity, while also raising ethical and methodological concerns.